Acute effects of a mavacamten-like myosin-inhibitor (MYK-581 in a feline model of obstructed hypertrophic cardiomyopathy: evidence of improved ventricular filling (beyond obstruction reprieve). (25th November 2020) - Ferguson, B.S; Stern, J.A; Oldach, M.S; Ueda, Y; Ontiveros, E.S; Napierski, N.C; Del Rio, C.L; Harris, S.P
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is a progressive disease characterized by cardiac remodeling, hyperdynamic contraction, and impaired ventricular filling that can lead to dynamic left-ventricular outflow-track (LVOT) obstruction and exertional intolerance. Direct myosin-inhibition with mavacamten can normalize contractility and improve exercise capacity in patients with oHCM, providing sustained symptomatic relief. However, mavacamten can also improve ventricular filling by limiting residual cross-bridges during diastole, and therefore, may offer cardiac benefits beyond obstruction reprieve. This study leveraged a feline model of oHCM, cats with the A31P MYBPC3 variant, to study the acute in vivo effects of MYK-581, a mavacamten surrogate, on cardiac hemodynamics and filling. Methods: A31P-homozygous cats with HCM (A31P, n=10) and wild-type healthy controls (CTRL, n=9) were anesthetized and instrumented for invasive pressure-volume (PV) measurements as well as trans-thoracic echocardiographic recording. A subset of cats were assigned to receive either vehicle (VEH, n=7) or MYK-581 (MYK, n=8) with a short IV infusion. Cardiac hemodynamics, function, and geometry were assessed at steady state before and during dobutamine challenges (2.5 μg/kg/min IV). Results: A31P cats had thicker ventricular walls (6.4±0.1 vs. 5.2±0.2 mm, P<0.05) and hyperdynamic contraction (FS: 61±4 vs. 50±3%, P<0.05) relative to controls and presented with dynamic LVOT obstruction in 54% of cases. HCM cats had elevated end-diastolic pressures (17±1.4 vs. 9±1.0 mmHg, P<0.05), with prolonged time constants of relaxation (60±4.1 vs. 36±2.4 ms, P<0.05) and elevated end-diastolic stiffness (Eed: 0.44±0.06 vs. 0.25±0.01 mmHg/mL). Acute treatment with MYK-581 alleviated LVOT obstruction (0% vs. 38%), normalized contractility (FS: −7±2%), and increased systolic/diastolic chamber dimensions (e.g., LVIDd: +13±4%) (all P<0.05), while reducing EDP (15±2 to 13±2 mmHg, P<0.05), suggesting acute improvement in ventricular distensibility. Indeed, MYK-581 treatment reduced end-diastolic stiffness (Eed: 0.48±0.11 vs. 0.36±0. 10 mmHg/mL, P<0.05) and normalized trans-mitral motion patterns during filling. Conclusions: Bred cats, homozygous for the A31P MYBPC3 variant, presented a cardiac phenotype that models multiple characteristics of the human oHCM phenotype including dynamic LVOT obstruction. Acute treatment with the mavacamten surrogate, MYK-581, not only alleviated hypercontractility and LVOT obstruction, but improved ventricular filling and end-diastolic pressures. Taken together, these pre-clinical observations show potential salutary effects beyond obstruction relief in patients with HCM. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): MyoKardia